O-184 The impact of cryopreserved sperm on Intrauterine Insemination (IUI) outcomes: Is frozen as good as fresh?. (30th June 2022) - Cherouveim, P; Vagios, S; Hammer, K; Fitz, V; Jiang, V; James, K; Dimitriadis, I; Bormann, C; Souter, I
Abstract: Study question: Are the outcomes of IUI cycles [with or without ovarian stimulation (OS)] comparable when frozen instead of fresh-ejaculated sperm is utilized? Summary answer: Overall, clinical outcomes did not differ significantly between frozen and fresh sperm IUI cycles, although specific subgroups might benefit from fresh sperm utilization. What is known already: At present, data from animal studies point towards less favorable outcomes with frozen sperm utilization, implicating cryopreservation-induced damages to the cytoskeleton, DNA, and acrosome leading to adverse effects on spermatozoa's motility, viability, and ability to fuse with the oocyte. Assisted Reproductive Technology (ART) data, mostly focusing on severe male factor infertility diagnoses, suggest no major differences between in-vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles utilizing frozen over fresh sperm, often surgically extracted. Nevertheless, contemporary data from IUI(±OS) cycles are still scarce. Study design, size, duration: Data from 5335 IUI(±OS) cycles (time-period: 01/2004-12/2021) from a large academic fertility center were retrospectively reviewed. Cycles were stratified in two groups based on utilization of frozen instead of fresh-ejaculated sperm for the IUI [ FROZEN (n = 1871, all infertility diagnoses), and FRESH (n = 3464, idiopathic infertility diagnosis only), respectively]. Cycle outcomes were compared between groups. Participants/materials, setting, methods: Participants: women seeking IUI (±OS) treatments. Outcome Measures: HCG-positivity, clinical pregnancy (CP), spontaneous abortion (SAB) rates. Initial analysis included all cycles irrespective of OS regimen.  Cycles were then stratified by OS regimen into three subgroups [injectable gonadotropins, oral medications (OM) : clomiphene-citrate and letrozole, and unstimulated/natural ]. Odds ratios (OR) for all relevant outcomes were calculated utilizing logistic regression and adjusted for maternal age, day-3 FSH, and OS regimen. Time-to-pregnancy and first-cycle only analyses were also performed. Main results and the role of chance: Unadjusted HCG-positivity, and CP were lower in the FROZEN compared to the FRESH group (12.2% vs. 15.6%, p < 0.001; 9.4% vs. 13.0%, p<.001, respectively), which persisted only among OM after stratification (9.9% vs. 14.2% HCG-positivity, p=.030; 8.1% vs. 11.8% CPR, p=.041, for FROZEN compared to FRESH, respectively). Among all cycles, adjOR(95%CI) for HCG-positivity and CP were respectively: 0.75(0.56-1.02), and 0.77(0.57-1.03), ref: FRESH ). Following stratification by OS regimen, adjOR(95%CI) for HCG-positivity and CP showed no difference between groups among gonadotropin and natural cycles but favored the FRESH group in OM cycles [HCG-positivity: 0.55(0.30-0.99); CP: 0.49(0.25-0.95), ref.: FRESH ]. SAB odds did not differ between groups among OM and natural cycles but were lower in the FROZEN compared to FRESH group among gonadotropin cycles [adjOR(95%CI): 0.13(0.02-0.98), ref.: FRESH ]. However, regarding the latter comparison, numbers were small and the 95%CI wide.  When analysis was limited to first-cycles only and further stratified by OS regimen, the previously noted differences in CP and SAB odds no longer existed within the OS subgroups. Nevetheless, time-to-conception was slightly longer in the FROZEN compared to the FRESH group (3.84 vs. 2.58 cycles, p<.001). Limitations, reasons for caution: Study is limited by its retrospective nature. The two groups differed somewhat in age, infertility diagnosis, utilized OS regimen, and as expected in total motile sperm counts. Despite the less favorable characteristics of the FROZEN group, no detrimental effect of sperm cryopreservation on IUI outcomes was noted. Wider implications of the findings: Our study, the largest to date, showed no significant difference in IUI outcomes between cycles utilizing frozen instead of fresh-ejaculated sperm. Although, specific subgroups might benefit from fresh sperm utilization and time-to-pregnancy might be shorter with fresh over frozen sperm, patients should be counselled about the non-inferiority of frozen sperm. Trial registration number: Not applicable